The Porphyry Column in Constantinople and Тhe Relics of the True Cross - Bralewski, Sławomir; Gucio, Katarzyna (Studia Ceranea, 2011)
The complicated fates of the Porphyry Column of emperor Constantine resemble the reach and difficult history of Constantinople, the New Rome and capital of the eastern Empire from its very beginnings. Perceived by the Constantinopolitans as both Christian and pagan monument, adorned with legends repeated and enriched by generations, it was always a landmark of the city. The article summarizes, compares and analyzes the accounts of Byzantine historians, showing continuity of tradition and the lasting role of the unique object in the very heart of political centre of the imperial capital.